PTH-028 Analysis Of Quality Outcomes Following Changing Bowel Preparation For Colonoscopy From Picolax To Moviprep In Nhs Lothian. (9th June 2014) - Noble, CL; Church, NI; Shand, AG; Lees, CW; Brodie, H; Greenhill, G; Kennedy, N
Abstract : Introduction: Using our global rating scale data from 2010 we observed that the quality of preparation for colonoscopy using Moviprep was superior to Picolax. Given this and the National patient safety alert issued in 2009 regarding bowel preparation 1, we decided to change the default bowel preparation from Picolax to Moviprep in NHS Lothian in 2012. Methods: The aim of this study was to prospectively audit the quality of Moviprep and Picolax preparation for colonoscopy and flexible sigmoidoscopy during two 3 month periods-before (March-May 2012, period 1) and after (November-January 2013, period 2) Moviprep was changed to the default preparation in NHS Lothian for colonoscopy. All patients who attended the Western General Hospital for colonoscopy and flexible sigmoidoscopy during the two periods were included. Cost effective analysis was also undertaken. Results: 1418 Colonoscopies and flexible sigmoidoscopies were carried out during period 1 and 1234 were carried out during period 2. 454 (32%) of the colonoscopies were carried out using Moviprep in period 1 and 973 (79%) in period 2. Poor quality preparation was significantly more common with Picolax preparation when compared to Moviprep in both period 1: 12 vs. 7% (p = 0.0037) and period 2: 13% vs. 5% (p < 0.0001). Repeat endoscopic procedures and completion imaging due to poor preparation fell from 44 (3.1%) in period 1 to 21 (1.7%)(p = 0.03) in period 2 following the change in default preparation to Moviprep. The estimated annual savings on repeat procedures and completion imaging across NHS Lothian of £89 000 offset the increased cost of Moviprep (£8.60 per patient vs. £3.65 for Picolax) of £23 265 annually. Conclusion: Changing to Moviprep as the default preparation for colonoscopy in NHS Lothian has resulted in significantly better quality bowel preparation. Furthermore fewer repeat procedures have been required resulting in more efficient use of scarce capacity and cost savings. Reference: 1 http://www.nrls.npsa.nhs.uk/resources/?entryid45=59869 Disclosure of Interest: None Declared.